MAKANAN DIMSUM DALAM KARYA FOOD PHOTOGRAPHY - I Dewa Gede Mahadita Sudaya; Amoga Lelo Octaviano; Anis Raharjo (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
Dimsum was originally a snack or snack for Chinese residents in the southern region, including Hong Kong, which is inhabited by Cantonese people, because of this, Cantonese people are called the creators of dimsum. Through photography based on this research, the author wants to add insight and knowledge of the community about what dimsum food is and to describe and explain photo works inspired by dimsum food. This research is qualitative research with the focus of research on dimsum food whose creation process is immortalized through food photography. The implementation is done by digging data, analyzing data and presenting the results of data analysis. The process of extracting data can be reached through the methods of observation, interviews, and documentation. The results of this study produce a work through visualizing images of dimsum food into a photo work with a modern feel. Through this research, readers or the general public can find an option in disseminating the promotion method of dimsum food.